Extraction and characterization of oils from Phaleria macrocarpa seed - Azmir, Jannatul (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2014)
Phaleria macrocarpa (local name: Mahkota Dewa) is being traditionally used as an important medicinal plant for centuries in Malaysia and Indonesia. Different parts of this plant have been studied by several researchers for the pharmacological activities and bioactive compounds. Apart from the bioactive compounds, the seed of this plant contains high amount of oil that is of more than half of its dry weight. The oil content of P. macrocarpa seed, fatty acids composition and physicochemical properties of the oil were determined in this study. The oil of P. macrocarpa seed was extracted by solvent extraction as a conventional method using n-hexane and by supercritical CO2 (scCO2) extraction as a non-conventional method. The extraction conditions were optimized for both techniques using central composite design (CCD) of response surface methodology (RSM). In solvent extraction, 72°C, 8.4 h and 10.9 ml/g solvent-to-feed ratio was the optimum condition whereas 72°C, 42 MPa and 4.5 ml/min CO2 flow rate was the optimum condition for scCO2 extraction. At optimized condition, oil yields were 55.68g/100g and 52.9g/100g of dry seeds obtained by solvent extraction and scCO2 extraction methods, respectively. The results have shown that 95% oil extracted without utilizing any hazardous organic solvents in a short period of time by scCO2 extraction technique. The experimental and predicted data from the second order polynomial model of RSM was fitted adequately with R2 of 0.97 and 0.99 for solvent extraction and scCO2 extraction, respectively. To compare the predictive quality of RSM, a feed forward artificial neural network (ANN) based on a multi-layer perceptron (MLP) was modeled for the oil yield. ANN was proven as of better predictive model for the seed oil extraction than the RSM as it had similar R2 value and lower absolute average deviation (AAD) compare to RSM. The fatty acid composition in terms of triglycerides of the extracted P. macrocarpa seed oil was analyzed by gas chromatography-mass spectroscopy (GC-MS). Five major fatty acids such as palmitic acid (C16:0), stearic acid (C18:0), oleic acid (C18:1), linoleic acid (C18:2) and eicosanoic acid (C20:1) were found in the P. macrocarpa seed oil. Oleic acid (18:1) was found to be the predominant fatty acid constituent with 43.84±0.52% of the total fatty acid constituents. On the other hand, the long chain fatty acid (eicosanoic acid, 0.7%) and polyunsaturated fatty acid with high percentage of linoleic acid (29.18±0.65%) were also determined in the P. macrocarpa seed oil. Moreover, the total unsaturated fatty acids were 73.62±1.41% whereas the saturated fatty acids were only 26.38±0.18% in this seed oil. Physicochemical properties of the P. macrocarpa seed oil were also determined and comparable with other claimed high grade vegetable oils such as sunflower oil, soybean oil, palm oil etc. Thus, the P. macrocarpa (Mahkota Dewa) seed oil could also be claimed as food and pharmaceutical grade oil.